Wind Bands as Cultural Tradition and Economic Opportunities in Transformation in Sincelejo (Sucre, Colombia) - Hernández, Patricia María Mendívil; Calderón, María Alexandra Gutiérrez (Journal of Ecohumanism, 2024)
Human interactions are permeated by multiple factors, including cultural practices, where music is a fundamental element. The objective of this study was to understand the cultural identity of traditional wind band music and its organisational capacity in Sincelejo, Sucre - Colombia. The methodology was framed under the qualitativeapproach with a case study design, and interviews were used to collect the information. The results indicate that traditional wind band music constitutes the cultural identity of the inhabitants of Sincelejo, reinforcing the sense of belonging and social cohesion; in terms of organisational capacity, the bands have been financially consolidated over the years, although it is still necessary to strengthen this aspect to guarantee their sustainability. In conclusion, traditional wind band music in Sincelejo plays a fundamental role in the preservation of cultural identity and social cohesion. However, greater structuring of its financial management is required to ensure the continuity and development of this cultural tradition.